PENGGUNAAN APLIKASI SIPAK DALAM LAYANAN PEMBUATAN AKTA KELAHIRAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BLITAR - Choirul Masna Affandi; Nunuk Latifah; Rani Arifah Normawati (Sultan Syarif Kasim State Islamic University, Riau, 2024)
This study aims to find out how the process of making a birth instrument using the SIPAK (Population Administration Service Information System) operation during the Covid-19 Epidemic at the Population and Civil Registry Office of Blitar City. The type of exploration used is descriptive qualitative. Data was collected through interviews, observation, and attestation. The collected data is also described according to the main points of the problem. The result of this exploration is the SIPAK operation is used in online birth instrument processing. The procedures and conditions have been explained in the operation. The preface of the operation was carried out through socialization, radio media, leaflets or flyers, and the installation of billboards at colorful crowded points in Blitar City. The problems faced in using the SIPAK operation are unstable internet networks, lack of public understanding of how the SIPAK operation works, the senior who can not use mobile phones, and the lack of socialization about the SIPAK operation to the public due to restrictions on the use of the SIPAK operation. conditioning during the Covid-19 epidemic.